1997
DOI: 10.1007/bf03348021
|View full text |Cite
|
Sign up to set email alerts
|

Lactose intolerance following antithyroid drug medications

Abstract: We recently observed 2 lactase-deficient women with Graves' disease who consistently developed severe diarrhea after ingestion of thionamide (methimazole and propylthiouracil) tablets containing lactose as carrier. The strict temporal relationship between ingestion of lactose-containing tablets and appearance of intestinal symptoms, as well as the absence of side effects following ingestion of methimazole tablets without lactose as carrier, provided the clue for the diagnosis. To our knowledge, severe diarrhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…In highly sensitive individuals, it has been reported that the symptoms may occur after ingestion of as little as 200 mg of lactose and different types of medications have been shown to cause LI and in addition affect compliance. 13,[26][27][28][29][30][31] This could easily be ingested by taking just a single dosage of several drug preparations. An example which is available in the UK is Budenofalk (Dr Falk) in which each 3 mg tablet contains 600 mg of lactose.…”
Section: Discussionmentioning
confidence: 99%
“…In highly sensitive individuals, it has been reported that the symptoms may occur after ingestion of as little as 200 mg of lactose and different types of medications have been shown to cause LI and in addition affect compliance. 13,[26][27][28][29][30][31] This could easily be ingested by taking just a single dosage of several drug preparations. An example which is available in the UK is Budenofalk (Dr Falk) in which each 3 mg tablet contains 600 mg of lactose.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of gastrointestinal symptoms after ingestion of a lactose containing drug in lactose maldigesters has been described only in a limited number of case reports, 17–20 and population studies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A gyógyszerek mintegy 30%-a mellékhatásként hasmenést okozhat: ennek okai igen változatosak. Néhány gyógyszerről azonban leírták, hogy tejcukorérzékenysé-get okozhatnak, illetve a meglévő LI tüneti exacerbatió-jához vezetnek (kromoglikát, propicil, metiltiouracil, kolchicin) [37,38]: esetbemutatásokról van szó, a téma szisztematikus áttekintése nem történt meg.…”
Section: Laktózintolerancia éS a Gyógyszerekunclassified